Connecting pH with body size in the marine gastropod Trophon geversianus in a latitudinal gradient along the south-western Atlantic coast - Malvé, Mariano Ezequiel (2018)
There is growing concern about the impact of contemporaneous ocean acidification on marine ecosystems, but strong evidence for predicting the consequences is still scant. We have used the gastropod Trophon geversianus as a study model for exploring the importance of oceanographic variables (sea surface temperature, chlorophyll a, oxygen, calcite and pH) on large-scale latitudinal variation in mean shell length and relative shell weight. Data were collected from a survey carried out in 34 sites along ~1600 km. Neither shell length nor relative shell weight showed any monotonic latitudinal trend, and the patterns of spatial variability were rather complex. After correcting for spatial autocorrelation, only pH showed a significant correlation with mean shell length and relative shell weight, but contrary to expectations, the association was negative in both cases. We hypothesize that this could mirror the negative effect of acidification on growth rate, which may cause larger asymptotic size. Latitudinal trends of body size variation are not easy to generalize using ecogeographic rules, and may be the result of a complex interaction of environmental drivers and life-history responses.